Three step synthesis of single diastereoisomers of the vicinal trifluoro motif - Brunet, Vincent A.; Slawin, Alexandra M. Z.; O'Hagan, David (Beilstein Journal of Organic Chemistry, 2009)
A three step route to single diastereoisomers of the vicinal trifluoromethyl motif is described. The route starts from either syn- or anti-α,β-epoxy alcohols and takes a direct approach in that each of the three steps introduces a fluorine atom in a regio- and stereo-specific manner. Starting from either the syn- or the anti-α,β-epoxy alcohol, stereospecific reactions generate two separate diastereoisomeric series of this motif. The route is a significant improvement on an earlier six step strategy.
Keywords: C–F bond; organo–fluorine chemistry; stereospecific fluorination; vicinal trifluoro motif

(untitled) - Purser, S.; Moore, P. R.; Swallow, S.; Gouverneur, V. (Chem. Soc. Rev., 2008)

Modern Fluoroorganic Chemistry: Synthesis, Reactivity, Applications - Kirsch, P. (Wiley-VCH, 2004)

(untitled) - Brunet, V. A.; O'Hagan, D. (Angew. Chem., Int. Ed., 2008)

(untitled) - O'Hagan, D. (Chem. Soc. Rev., 2008)

(untitled) - Hunter, L.; O'Hagan, D. (Org. Biomol. Chem., 2008)

(untitled) - Hunter, L.; Kirsch, P.; Slawin, A. M. Z.; O'Hagan, D. (Angew. Chem., Int. Ed., 2009)

(untitled) - Hunter, L.; O'Hagan, D.; Slawin, A. M. Z. (J. Am. Chem. Soc., 2006)

(untitled) - Hunter, L.; Kirsch, P.; Hamilton, J. T. G.; O'Hagan, D. (Org. Biomol. Chem., 2008)

(untitled) - Hunter, L.; Slawin, A. M. Z.; Kirsch, P.; O'Hagan, D. (Angew. Chem., Int. Ed., 2007)

(untitled) - Hunter, L.; O'Hagan, D.; Slawin, A. M. Z. (J. Am. Chem. Soc., 2006)

(untitled) - Nicoletti, M.; O'Hagan, D.; Slawin, A. M. Z. (J. Am. Chem. Soc., 2005)

(untitled) - Nicoletti, M.; Bremer, M.; Kirsch, P.; O'Hagan, D. (Chem. Commun., 2007)

(untitled) - Schaus, S. E.; Brandes, B. D.; Larrow, J. F.; Tokunaga, M.; Hansen, K. B.; Gould, A. E.; Furrow, M. E.; Jacobsen, E. N. (J. Am. Chem. Soc., 2002)

(untitled) - Martinelli, M. J.; Vaidyanathan, R.; Pawlak, J. M.; Nayyar, N. K.; Dhokte, U. P.; Doecke, C. W.; Zollars, L. M. H.; Moher, E. D.; Khau, V. V.; Košmrlj, B. (J. Am. Chem. Soc., 2002)

(untitled) - Trnka, T. M.; Grubbs, R. H. (Acc. Chem. Res., 2001)

(untitled) - Gao, Y.; Hanson, R. M.; Klunder, J. M.; Ko, S. Y.; Masamune, H.; Sharpless, K. B. (J. Am. Chem. Soc., 1987)

(untitled) - Lal, G. S.; Pez, G. P.; Pesaresi, R. J.; Prozonic, F. M.; Cheng, H. (J. Org. Chem., 1999)

(untitled) - Farran, D.; Slawin, A. M. Z.; Kirsch, P.; O'Hagan, D. (J. Org. Chem., 2009)

(untitled) - Yoneda, N. (Tetrahedron, 1991)

(untitled) - Olah, G. A.; Welch, J. T.; Vankar, Y. D.; Nojima, M.; Kerekes, I.; Olah, J. A. (J. Org. Chem., 1979)

(untitled) - Lakshmipathi, P.; Grée, D.; Grée, R. (Org. Lett., 2002)

(untitled) - Filmon, J.; Grée, D.; Grée, R. (J. Fluorine Chem., 2001)